Biografías escénicas: Mi vida después de Lola Arias - Hernández, Paola (Latin American Theatre Review, 2011)
This article proposes a new approach to documentary theatre of the 21st centurythrough the study of Vivi Tellas’s Biodramas project and a close analysis of the play Mi vidadespués by Lola Arias. While these works make use of archives—such as videos, testimonies,newspaper articles, and film—as the primary sources in the transmission of knowledge, thisarticle aims to explore the liminality involved in the selection of archives and how their subsequentstagings will be received and interpreted. This new focus on documentary theatre notonly expands the notions previously promulgated by Piscator and Weiss, but also representsthe ambiguous and arbitrary role that archives play in today’s society. (PH, article in Spanish)